Shanghai in the new economy of global flows shaping urban form and connectedness in the digital age - Salat, Serge (Journal of Architecture and Urbanism, 2017)
This paper is a contribution to the significant research program having developed around the concept of the global city over the last four decades in urban sociology and in political geography. Global cities can be defined both as places and as locations in a network of flows. We use a network and complexity theory perspective to contribute to the debate about global cities and we apply this approach to a rising global city: Shanghai. Cities are networks from which locations emerge, and global cities are the places that emerge as interconnected command centres in the most dynamic and connected nodes in the global network of flows. As places, global cities present a highly unequal landscape of economic growth at intra-urban scale, with peaks of extreme concentration of wealth creation in specific locations within their urban space. To acquire a similar intensity of agglomeration economies in high-end services and in finance as global cities such as London, New York, Tokyo, Seoul, Singapore, and Hong Kong, Shanghai spatial structure needs more concentration and a more complex articulation of its economic densities. Pareto distributions, which are the “signature” of complexity, are the hidden order of the spiky spatial economic landscapes of global cities, for the distribution of people, jobs, and economic densities, office space density, accessibility to jobs, rents, subway network centralities. Within the dynamics of global networks, Shanghai challenge is to become a hub across five flows of goods, services, finance, people, and data and communication, in which Singapore and Hong Kong have acquired dominant positions as waypoints. The transformation of the global landscape of flows with an increasing growth of knowledge-based flows, cross-border flows, and digital flows puts Shanghai business model, dominated today by goods flows, at risk. Shanghai would benefit developing stronger air and Internet connectivity and building collaborative bridges with global cities.